2014
DOI: 10.1590/s1679-45082014ao2825
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain related to quality of sleep

Abstract: Objective:To determine the relation between the degrees of chronic pain and drowsiness levels.Methods:The study was conducted with 115 patients, who answered the questionnaire as diagnostic criteria in the survey. After evaluation based on the protocol of chronic pain registry RDC/TMD- Axis II, the Epworth Sleepiness Scale was applied to assess drowsiness levels.Results:Among the participating patients, there were more females (80%), and the type of pain more prevalent was chronic (70.4%). Concerning the grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Studies on sleep and pain in athletes are scarce. When observed in other populations, such as fibromyalgia patients, there is similarity of results indicating that better sleep quality is associated to less pain sensation, as reported by Marta et al 33 ; Moldofsky 34 ; Tonial, Stechman Neto & Hummig 35 . According to the prevalence of musculoskeletal complaints impairing the most the performance of daily life activities of athletes in the last 12 months, there are knees, shoulders, low back and ankles/feet.…”
Section: Discussionsupporting
confidence: 73%
“…Studies on sleep and pain in athletes are scarce. When observed in other populations, such as fibromyalgia patients, there is similarity of results indicating that better sleep quality is associated to less pain sensation, as reported by Marta et al 33 ; Moldofsky 34 ; Tonial, Stechman Neto & Hummig 35 . According to the prevalence of musculoskeletal complaints impairing the most the performance of daily life activities of athletes in the last 12 months, there are knees, shoulders, low back and ankles/feet.…”
Section: Discussionsupporting
confidence: 73%
“…While we did not find any significant difference in daytime sleepiness of our patients, this seems to be in accordance with a study conducted in Brazil relating degrees of chronic pain to drowsiness levels. Although they noted their patients were sleep deprived, they also found that ESS scores were similar across all patients with varying degrees of chronic pain (30). In a study comparing insomnia patients to a control group found that daytime sleepiness in insomnia patients was similar to that of the control group (31).…”
Section: Discussionmentioning
confidence: 96%
“…In a young (ages [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], healthy patient population screened for sleep disorders and sleep efficiency of >85% (total sleep time/time in bed), participants were randomly assigned to either continue their normal sleep regime, or extend their sleep to ten hours nightly for four consecutive days. Pain sensitivity assessments were performed on experimental day one and day four.…”
Section: Introductionmentioning
confidence: 99%
“…Perception of pain can be the result of multisystemic involvement, psychological distress, and related disability. Pain negatively influences everyday life and activities, alters behavioral profiles, impairs sleeping patterns, and diminishes quality of life and functional capabilities (Blake et al, ; Tonial et al, ). These observations have been confirmed by previous studies on selected samples of individuals (Houlihan et al, ; Liedberg, Björk, & Börsbo, ; Pimentel, Gui, Reimão, & Rizzatti‐Barbosa, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pain represents a psychosomatic experience resulting in physical, psychical, and emotional sufferance. Persistent pain causes suffering, distress, deterioration of quality of life (QoL) (Houlihan, O'Donnell, Conaway, & Stevenson, ), abnormal sleeping patterns (Blake et al, ; Tonial, Stechman Neto, & Hummig, ), and anatomic changes of sensory perception (Curatolo & Arendt‐Nielsen, ). While individuals with intelligence quotient (IQ) within the normal range do not have difficulties complaining about presence, localization, and intensity of painful stimuli, the same characteristics are difficult to be reported by noncommunicating children or intellectually impaired individuals (Breau & Burkitt, ).…”
Section: Introductionmentioning
confidence: 99%